2012
DOI: 10.1002/hep.25890
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling reveals hepatic stem-like gene signatures and interplay of miR-200c and epithelial-mesenchymal transition in intrahepatic cholangiocarcinoma

Abstract: Intrahepatic cholangiocellular carcinoma (ICC) is the second most common type of primary liver cancer. However, its tumor heterogeneity and molecular characteristics are largely unknown. In this study, we conducted transcriptomic profiling of 23 ICC and combined hepatocellular cholangiocarcinoma tumor specimens from Asian patients using Affymetrix mRNA and Nanostring microRNA microarrays to search for unique gene signatures linked to tumor subtypes and patient prognosis. We validated the signatures in addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
183
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(197 citation statements)
references
References 49 publications
(50 reference statements)
6
183
1
3
Order By: Relevance
“…This raises the possibility that mutant IDH1/2-and 2-HGmediated EMT may play a role in the pathology of these epithelial tumors, with cholangiocarcinoma in particular. Notably, a recent study finds that a subset of intrahepatic cholangiocarcinoma exhibit aspects of EMT, with miR-200c reduction as a central phenotype (61). It will be intriguing to determine whether IDH mutations track with this subtype of cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the possibility that mutant IDH1/2-and 2-HGmediated EMT may play a role in the pathology of these epithelial tumors, with cholangiocarcinoma in particular. Notably, a recent study finds that a subset of intrahepatic cholangiocarcinoma exhibit aspects of EMT, with miR-200c reduction as a central phenotype (61). It will be intriguing to determine whether IDH mutations track with this subtype of cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients with IDH1 and IDH2 mutations were significantly enriched in P2-P3 subgroups of our proliferation subclass (15/45 versus 3/62 rest, Po0.001, Fisher's exact test, Fig. 6), which is associated with chromosomal instability, enrichment of a stem cell-like iCCA signature 27 and activation of EGFR signalling. Consistent with the functions of IDH1/2 enzymes, the pathways related to tricarboxylic acid cycle and electron transport were enriched in patients with IDH mutations (FDRo0.05, Supplementary Table 11).…”
Section: T C a C A A C C A A T G A G -G A T G G C T A C A A T A G T Cmentioning
confidence: 90%
“…Consistent with the functions of IDH1/2 enzymes, the pathways related to tricarboxylic acid cycle and electron transport were enriched in patients with IDH mutations (FDRo0.05, Supplementary Table 11). Moreover, a recently published iCCA signature with stem cell-like features 27 was significantly enriched in IDH mutant tumours 28 along with several oncogenic pathways including KRAS, MET, NOTCH and VEGF pathways. iCCA tumours harbouring the FGFR2 fusions did not show significant enrichment in any of the iCCA subclasses (Fig.…”
Section: T C a C A A C C A A T G A G -G A T G G C T A C A A T A G T Cmentioning
confidence: 99%
“…However, few new markers associated with prognosis or malignant behavior of ICC has been determined (Oishi et al 2012;Shimada et al 2010). In this study we studied Nogo-B, which has recently been identified as a potential marker of hepatic fibrosis (Zhang et al 2011;Gao et al 2013;Tashiro et al 2013;Men et al 2015) and as a potential enhancer of bile duct proliferation (Zhang Each survival rate is shown as % value, based on our analytical software.…”
Section: Macroscopic Findingmentioning
confidence: 99%